Physical activity recommendation by cardiologists. (11th May 2021) - Davolos, I; Franchella, J; Iglesias, D; Paz, I; Sayavedra, G; Sotelo, B; Gelormini, A; Pappalettere, C; Bucay, C; Castiello, G; Gonzalez Naya, E; Stuart, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Exercise Cardiology Council Background. Large number of studies confirm benefits of physical activity (PA) to improve health. Recommendation guidelines lack tools for health professionals training in PA prescription. Purpose. To show cardiologists knowledge degree and attitude regarding existing recommendations on PA. Methods. Observational and cross-sectional study. n = 299. A virtual survey describes cardiologist profile, knowledge degree, planning and satisfaction while making PA recommendation. Results.  Cardiologists profile in Table 1. Mean age 47.27 (SD 11.92). Sedentary lifestyle is considered a cardiovascular risk factor (CVRF) by 93.24%. 70% report performing PA complying with the recommendations of world health organization. 98.99% recommend PA while 80.74% also prescribe it. Prescribing PA, cardiologists self-rating is adequate-very adequate in 83%. Instruments used are guidelines (57.33%), self-perception (32%), expert opinion (25.33%). Most suggested mode of exercise is walking or jogging. Only 25.67% combine resistance and strength exercises. Only 13% choose to combine four parameters (heart rate, time, mode, intensity). Only 31.85% have undergone postgraduate training or education on PA prescription.  Conclusions.  Approximately 25% of cardiologists use valid or formal indicators to prescribe PA. Cardiologist with CVRF perform less PA than the rest. It is observed that PA prescription is influenced by PA degree performed by the physician. Lack of training seems to be the biggest obstacle to PA prescription generalization.